In what ways are teacher candidates being prepared to teach about the environment? A case study from Wisconsin. Issue 3 (16th March 2017) - Ashmann, Scott; Franzen, Rebecca L.
Abstract : There is an urgent need for primary and secondary students to develop awareness, knowledge, attitudes, and an environmental ethic necessary to undertake environmental issues and problems. The need to adequately prepare teachers to teach about the environment, and the challenges the field of environmental education (EE) faces lead us to the research question: In what ways are teacher candidates being prepared to teach primary and secondary students about the environment? Using a case study approach of the 33 teacher education programs in Wisconsin (USA), we explored the ways in which EE is integrated into teacher preparation. Surveys, interviews, and the analysis of course documents (e.g. syllabi, assignment sheets) were used to identify two primary ways in which EE is being integrated – courses and activities. After examining the commonalities among programs that are doing more than typical (such as using multiple ways to include EE or having high quality EE), we explored the role organizational resources – material, human, and social – play in teacher education programs.